Analisis Implementasi Peran Komisi Penyiaran Indonesia Dalam Penerapan P3sps Terhadap Keberpihakan Media Siaran Program Pemilu Edisi 2024 - Muhammad Alif Utama; Asep Gunawan; Gunawan Ikhtiono (KOLONI, 2024)
Television and radio broadcast media are the main means for various political actors to promote the candidates they support, as well as the political ideas they use. This can also have a negative impact in the world of broadcasting, such as unbalanced reporting, divisions between communities, and even black campaigns. Therefore, the role of the KPI as a state institution that oversees broadcasting activities in Indonesia is really needed, especially in election years the issue that always circulates regarding media impartiality. This research aims to find out the KPI strategy in overcoming broadcast media bias. This research uses a qualitative descriptive method with a case study type of research, where the data search uses observation, in-depth interviews and documentation, and then the data presentation uses descriptive. The results of this research, firstly, are that the strategy carried out by KPI to overcome media bias is: a) Creating an election task force with Bawaslu, KPU, and the press council to speed up law enforcement, b) Then providing appeals and outreach to all broadcasting institutions to comply with regulations. . election, P3SPS, and PKPI number 4 of 2024, c) Data on the number of news reports, running texts and advertisements featuring election participants or parties